Particular features of lipid metabolism in psoriasis patients with concomitant metabolic syndrome - A. G. Pashinyan; YE. V. Dontsova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To assess particular features of lipid metabolism in psoriasis patients with concomitant metabolic syndrome (MS). Materials and methods. Total cholesterol, triglycerides (TG) and high density lipoprotein cholesterol (HDL cholesterol) were determined in the blood serum of psoriasis patients by the enzymatic method using a spectrophotometer at the wavelength of 500 nm. The level of low-density lipoprotein cholesterol (LDL cholesterol) was determined by the calculation method using W. Friedewald's formula (1972). The cholesterol atherogenicity ratio (CAR) was calculated by the formula: CAR = (Total cholesterol - HDL cholesterol) / HDL cholesterol Results. Patients suffering from psoriasis vulgaris are distinguished by lipid metabolism abnormalities characterized by the development of atherogenic dyslipidemia, increase in the total cholesterol, TG and LDL cholesterol in blood, reduction in the HDL cholesterol level and increased CAR. Patients with concomitant metabolic disorders have more obvious changes.